A study on the coagulation factor XIII and other haemostatic markers in neurosurgical patients - Hussin, Suryati (2010)
Abnormalities of haemostatic system can lead to bleeding complication or thromboembolic events which can cause severe impairment or even death of neurosurgical patients. Therefore an optimal functional integrity of the hemostatic system is a prerequisite for the safe performance of neurosurgical procedures. To monitor the individual coagulation capacity of each patient, standard tests are effective to detect deficiencies involving the generation of fibrin. However, fibrin clot strength depends primarily on coagulation factor XIII, which cross-links fibrin monomers and enhances clot resistance against fibrinolysis. Currently, factor XIII activity levels are not routinely screened prior to surgical interventions and no effective screening test available to detect deficiency state. Therefore, the objective of this prospective study was to determine the clinical relevance of perioperative factor XIII activity levels and other haemostatic markers with postoperative haematoma formation in neurosurgical patients. Neurosurgical patients who required intracranial surgery from January 2008 until Jun 2009 were admitted to the study. All included patients had their blood taken at preoperatively and within 24 hours postsurgical periods for platelet count, PT/INR, aPTT, fibrinogen, factor XIII, antithrombin and PAI-1 levels. Intracranial surgeries were proceeded according to the standard neurosurgical techniques. All operated patients had their CT brain scan done after the surgery. The post operative CT brain scan determined the presence or absence of postoperative haematoma. Based upon these CT brain findings, patients were subclassified into 3 groups; significant haematoma, insignificant haematoma and no haematoma groups. The commercially available software SPSS Inc, version 12.0 was used in statistical analysis and probability values < 0.05 were considered significant. A total of 84 patients were enrolled in this study. Fifty one patients did not have postoperative haematoma, 28 patients developed insignificant postoperative haematoma and 5 patients did have significant postoperative haematoma. Haematological tests for platelet count, PT/INR and factor XIII activity levels showed significant differences between pre and postoperative values. However, only postoperative platelet count was turned out to be significant and related to postoperative haematoma formation. Low platelet and antithrombin levels were the only two parameters that had significant association with increased risk for postoperative haematoma. Interestingly, combination of low platelets count and low factor XIII activity levels contribute a significantly higher odd ratio of having postoperative bleeding complications. Similarly, combination of low postoperative antithrombin and factor XIII activities also increased the odds of developing haematoma. This study proved that presence of multiple defects in haemostatic markers, play an important role in the formation of significant postoperative haematoma for neurosurgical patients. In fact, five patients who developed significant postoperative haematoma did have low values for some of these markers. Platelet count, factor XIII and antithrombin activities were hardly monitored during intracranial surgery. These haemostatic markers tend to get compromised after complex cranial surgery leading to bleeding complication. The results of this study indicated that few coagulation markers which are platelet count, factor XIII and antithrombin activities might serve to improve management in patients with intracranial surgery. Monitoring these parameters prior or post intracranial surgery, will allow the neurosurgeon to evaluate the risk of haematoma following the surgery. Studies in the usefulness of blood products like platelet, antithrombin and factor XIII concentrates could be considered in future based on these findings.